Bacillus coagulans tolerance to 1‐ethyl‐3‐methylimidazolium‐based ionic liquids in aqueous and solid‐state thermophilic culture. (11th January 2014) - Simmons, Christopher W.; Reddy, Amitha P.; VanderGheynst, Jean S.; Simmons, Blake A.; Singer, Steven W.
<x xml:space="preserve">Abstract</x> The use of ionic liquids (ILs) to disrupt the recalcitrant structure of lignocellulose and make polysaccharides accessible to hydrolytic enzymes is an emerging technology for biomass pretreatment in lignocellulosic biofuel production. Despite efforts to reclaim and recycle IL from pretreated biomass, residual IL can be inhibitory to microorganisms used for downstream fermentation. As a result, pathways for IL tolerance are needed to improve the activity of fermentative organisms in the presence of IL. In this study, microbial communities from compost were cultured under high‐solids and thermophilic conditions in the presence of 1‐ethyl‐3‐methylimidazolium‐based ILs to enrich for IL‐tolerant microorganisms. A strain of Bacillus coagulans isolated from an IL‐tolerant community was grown in liquid and solid‐state culture in the presence of the ILs 1‐ethyl‐3‐methylimidazolium acetate ([C2mim][OAc]) or 1‐ethyl‐3‐methylimidazolium chloride ([C2mim][Cl]) to gauge IL tolerance. Viability and respiration varied with the concentration of IL applied and the type of IL used. B. coagulans maintained growth and respiration in the presence of 4 wt% IL, a concentration similar to that present on IL‐pretreated biomass. In the presence of both [C2mim][OAc] and [C2mim][Cl] in liquid culture, B. coagulans grew at a rate approximately half that observed in the absence of IL. However, in solid‐state culture, the bacteria were significantly more tolerant to [C2mim][Cl] compared with [C2mim][OAc]. B. coagulans tolerance to IL under industrially relevant conditions makes it a promising bacterium for understanding mechanisms of IL tolerance and discovering IL tolerance pathways for use in other microorganisms, particularly those used in bioconversion of IL‐pretreated plant biomass. © 2013 American Institute of Chemical Engineers Biotechnol. Prog., 30:311–316, 2014